MOLECULAR DYNAMICS MODELING OF STISHOVITE - Luo S.N.; Cagin T.; Strachan A.; Goddard W.A.; Ahrens T.J. (My University, 2002)
A Morse-stretch potential charge equilibrium force field for silica system has been employed to simulate the thermodynamics of stishovite with the molecular dynamics (MD) method. The equation of state, thermal expansivity and melting curve of stishovite have been obtained. This simple force field yielded results in accordance with the static and dynamic experiments. The stishovite melting simulation appears to validate the interpretation of superheating of the solid along the Hugoniot in the shock melting experiments. MD simulations show that the thermal expansivity of stishovite at lowermost mantle conditions is a weak function of temperature. The phase diagram of silica up to the mega bar regime is proposed based on the experimental and theoretical studies. The related physical and geophysical implications are addressed.
Keywords: THERMODYNAMIC PROPERTIES; EQUATIONS OF STATE; STISHOVITE; SILICA; MELTING